Antimicrobial resistance in Escherichia coli isolates from Japanese raccoon dogs (Nyctereutes viverrinus) in Kanagawa Prefecture, Japan: Emergence of extended-spectrum cephalosporin-resistant human-related clones. Issue 12 (16th December 2022) - Shimizu, Takae; Kido, Nobuhide; Miyashita, Naoki; Tanaka, Sohei; Omiya, Tomoko; Morikaku, Kouki; Kawahara, Minori; Harada, Kazuki
Abstract : Introduction. Wild animals are one of the putative reservoirs of antimicrobial-resistant bacteria, but the significance of raccoon dogs remains to be investigated. Hypothesis. Raccoon dogs can be a reservoir of antimicrobial-resistant bacteria. Aim. This study aimed to explore the prevalence of antimicrobial resistance, mainly extended-spectrum cephalosporins resistance, in Escherichia coli isolates from faeces of 80 Japanese raccoon dogs in Kanagawa Prefecture, Japan. Methodology. All of the 80 faecal samples were streaked onto deoxycholate-hydrogen sulfate-lactose (DHL) and cefotaxime (CTX)-supplemented DHL (DHL-CTX) agars. Susceptibilities to ten antimicrobials were determined using the agar dilution method. Additionally, extended-spectrum β-lactamases (ESBLs) and AmpC-type β-lactamases (ABLs) were identified in addition to sequence types (STs), in ESC-resistant isolates by a polymerase chain reaction and sequencing. Results. Out of all the samples, 75 (93.8 %) and 20 (25.0 %) E. coli isolates were isolated by DHL and DHL-CTX agars, respectively. Significantly higher resistance rates to most of the drugs were found in DHL-CTX-derived isolates than DHL-derived isolates ( P <0.01). Genetic analysis identified CTX-M-14 ( n =6), CTX-M-2 ( n =2), CTX-M-1 ( n =1) and CTX-M-55 ( n =1) as ESBLs, and CMY-2 ( n =8) and DHA-1 ( n =1) as ABLs in 20 DHL-CTX-derived isolates. Most of the detected STs were related to Japanese humans (i.e. ST10, ST58, ST69, ST131, ST357, ST648 and ST4038). Notably, this is the first report on ST69, ST131, ST155 and ST648, which are well-known international high-risk clones in Japanese raccoon dogs. Conclusion. Our findings underscore the need to understand the significance of raccoon dogs as an antimicrobial-resistant bacteria reservoir using one health approach.